2011
DOI: 10.1002/0471140856.tx0311s48
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Assays for Assessing Mitochondrial Dysfunction Caused by Compounds that Impair mtDNA‐Encoded Protein Levels in Eukaryotic Cells

Abstract: Compounds that impair the synthesis of either mitochondrial DNA (mtNDA) or mtDNA-encoded proteins reduce the levels of 13 proteins essential for oxidative phosphorylation, leading to a decrease in mitochondrial ATP production. Toxicity caused by these compounds is seldom identified in 24 to 72 hr cytotoxicity assays due to the low turnover rates of both mtDNA and mtDNA-encoded proteins. Here, we describe three high-throughput screening assays that detect compounds that affect mtDNA-encoded protein levels. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Hyperpolarization of DJ m is associated with higher energy demand, as found in differentiating neuroblasts (Voccoli and Colombaioni, 2009), dividing versus quiescent cells (Huang, 2002), and developmentally active cells (Daniele et al, 2017;Medina et al, 2002). Depolarization of DJ m is associated with diseased cells, aging, apoptosis, and toxic insults (Lezi and Swerdlow, 2012;Nadanaciva et al, 2011;Nicholls, 2004;Wagner et al, 2008). We measured DJ m and then ATP production in cultured neurons to identify chemicals that increase the functional output of mitochondria.…”
Section: Primary Neuron Assays For Inner Mitochondrial Potential and Atp Generationmentioning
confidence: 99%
“…Hyperpolarization of DJ m is associated with higher energy demand, as found in differentiating neuroblasts (Voccoli and Colombaioni, 2009), dividing versus quiescent cells (Huang, 2002), and developmentally active cells (Daniele et al, 2017;Medina et al, 2002). Depolarization of DJ m is associated with diseased cells, aging, apoptosis, and toxic insults (Lezi and Swerdlow, 2012;Nadanaciva et al, 2011;Nicholls, 2004;Wagner et al, 2008). We measured DJ m and then ATP production in cultured neurons to identify chemicals that increase the functional output of mitochondria.…”
Section: Primary Neuron Assays For Inner Mitochondrial Potential and Atp Generationmentioning
confidence: 99%
“…; Nadanaciva et al. ; Kumar et al. ), and here it was suggested that it has further merit as a reliable application in whole‐tissue section histological processing and quantification.…”
Section: Resultsmentioning
confidence: 77%
“…Most likely, high energy-demanding tissues (such as the neurons of the CNS) require lower thresholds of mutated mtDNA to result in bioenergetic depletion. Depletion of mtDNA can also cause disrupted mtDNA protein synthesis and thus leads to insufficient energy production in the affected cells [34]. Furthermore, nDNA variation could be mainly responsible for these mtDNA changes, given the importance of nDNAencoded genes in mtDNA-related processes [35].…”
Section: A Primer On Mitochondrial Biologymentioning
confidence: 99%